Pengaruh Model Pembelajaran Case Based Learning Terhadap Kemampuan Menulis Teks Eksplanasi Pada Siswa Kelas XI SMA Negeri 3 Medan - Enjelita Sormin; Muhammad Surip (Pusat Riset dan Inovasi Nasional, 2024)
This research was carried out with the aim of finding out the effect of the Case Based Learning learning model on the ability to write explanatory text. The population of this study was all students of class XI SMA Negeri 3 Medan, totaling 6 classes. Sampling in this study was carried out randomly, so 2 classes were obtained, namely class XI MIA-2 consisting of 30 students as the experimental class and class XI MIA-5 consisting of 30 students as the control class. From the data collection and processing that has been carried out, it shows that the ability to write explanatory text in class using the conventional model obtained an average value of 67.08 and a standard deviation of 9.87. Apart from that, judging from the normality test results of the Case Based Learning learning model, the results were Lcount<Ltable, namely 0.137<0.161. Then in the conventional learning model Lcount<Ltable is 0.124<0.161. Because Lcount is smaller than Ltable, the two data above are said to be normally distributed. Likewise, from the results of the data homogeneity test, namely Fcount<Ftable, namely 0.51<0.53, the data comes from a homogeneous population. After the normality test and homogeneity test, hypothesis testing is then carried out. From hypothesis testing, the results obtained are Tcount>Ttable with hypothesis test results of 5.85>1.699, then Ho is rejected and Ha is accepted so this proves that the Case Based Learning model is more influential in improving the ability to write explanatory text in class XI students at SMA Negeri 3 Medan .